Pharmacologically effective red yeast rice preparations marketed as dietary supplements illustrated by a case report. Issue 3 (26th January 2016) - Venhuis, B.J.; van Hunsel, F.; van de Koppel, S.; Keizers, P.H.J.; Jeurissen, S.M.F.; De Kaste, D.
Abstract : This paper reports a typical statin‐related adverse reaction from a red yeast rice (RYR) supplement and the analytical findings from the supplement. It also examines the regulatory framework governing botanical supplements in Europe. Two key events that shaped the current regulatory framework are reviewed. First, the Hecht‐Pharma judgement by the European Court of Justice (ECJ) that inverted the precautionary principle in the Medicines Act to a reactionary principle. Following the Hecht‐Pharma judgement, pharmacological active dietary supplements can be sold until sufficient signals of harm show that they are an unregistered medicine, placing a huge burden on regulatory authorities. Secondly, the European Food Safety Authority (EFSA) in 2011 approved the first health claim for pharmacologically active RYR dietary supplements. If the current regulatory status for pharmacologically active RYR dietary supplements does not permit adequate warning and active monitoring of adverse drug reactions, then the current regulatory framework may not be adequate to ensure consumer safety.Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A recent case report of a typical statin‐related adverse drug reaction after taking a red yeast rice (RYR) dietary supplement prompted the assessment of its regulatory status. This perspective describes the analysis of the patient's remaining capsules and examines two key events that have contributed to the marketing of pharmacologically effective dietary supplements in the European Union (EU).